Pengaruh Penggunaan Media Flash Card terhadap Keterampilan Membaca Permulaan pada Siswa Kelas II di SD IT Ummu Fathima Kota Bengkulu - Heru Frayetno; Bobi Endiko Saputra; Yosi Yoliza; Andre Taulani (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
This study aims to determine the effect of using flashcards on the early reading skills of second-grade students at SD IT Ummu Fathima, Bengkulu City. The study employs a quantitative approach using a quasi-experimental design—specifically, a non-equivalent control group design. The study population consisted of all students at SD IT Ummu Fathima, Bengkulu City, while the sample comprised 40 students: 20 from class IIA (experimental group) and 20 from class IIB (control group). Data collection techniques included observation, testing, and documentation. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing (Independent Sample t-test) with the aid of IBM SPSS Statistics Version 25. The results indicate that the implementation of instruction using flashcards improved with each session, ranging from